Molecular Mechanisms of Colistin Resistance in Klebsiella pneumoniae in a Tertiary Care Teaching Hospital - Liu, Yanling; Lin, Yiqing; Wang, Ziwen; Hu, Niya; Liu, Qiong; Zhou, Wenkai; Li, Xiuzhen; Hu, Longhua; Guo, Jian; Huang, Xiaotian; Zeng, Lingbing (Frontiers in Cellular and Infection Microbiology, 2021)
Background Over the last two decades, the prevalence of colistin resistance among the members of Enterobacteriaceae has been increasing, particularly among Klebsiella pneumoniae isolates; this limits the potential use of colistin and leads to worsened clinical outcomes. Methods We investigated the prevalence and genetic characteristics of colistin-resistant K. pneumoniae (COLR-KP) in clinical isolates using genomic sequencing. Results In total, 53 K. pneumoniae isolates (4.5%, 53/1,171) were confirmed as COLR-KP, of which eight isolates carried mobile colistin-resistant (mcr) gene. Although the overall prevalence rate (0.7%, 8/1,171) of mcr-like genes in clinical K. pneumoniae remained relatively low, the presence of mcr (15.1%, 8/53) among the COLR-KP isolates indicated that the mobile resistance gene was already widespread among K. pneumoniae isolates in hospital setting. We randomly selected 13 COLR-KP isolates (four mcr-bearing and nine non-mcr-bearing isolates) for whole-genome sequencing, including two pandrug-resistant and four sequence type 11 (ST11) isolates. Phylogenetic analysis revealed that all COLR-KP isolates were genetically diverse. Among the four mcr-bearing isolates, three (KP4, KP18, and KP30) were positive for mcr-1 and one (KP23) for mcr-8; none of the other mcr genes were detected. The mcr-1 in the KP4 and KP30 isolates were located in an IncX4 plasmid (approximately 33 kb) and could be successfully transferred to Escherichia coli J53AZR. In contrast, for the mcr-8-bearing plasmid in KP23 (IncFII), colistin resistance could not be transferred by conjugation. The mcr-1-producing isolate KP18 coexists a novel plasmid-carried tigecycline resistance gene tmexCD1-toprJ1. The most common chromosomal mutation associated with colistin resistance was a T246A amino acid substitution in PmrB, which was identified in most COLR-KP isolates (11/13, 84.6%). All ST11 isolates additionally had an R256G amino acid substitution. Critical virulence factors associated with hypervirulent K. pneumoniae were detected in four COLR-KP isolates; these virulence factors included aerobactin, salmochelin, and yersiniabactin. Conclusion We found that mcr-bearing COLR-KP emerged in our hospital and was growing at an increasing rate. Simultaneous emergence of hypervirulence and colistin–tigecycline–carbapenem resistance in the epidemic clone ST11 K. pneumoniae was also observed; this highlights the significance of active and continuous surveillance.